The analysis of schizophrenia-like psychosis in dentatorubral-pallidoluysian atrophy - Ikegami, Ichiko; Mitsuhashi Koike, Yuka; Hayashi, Hideki; Hirokawa, Sachiko; Ando, Shoichiro; Ishihara, Tomohiko; Onodera, Osamu (Frontiers in Neurology, 2025)
BackgroundDentatorubral-pallidoluysian atrophy (DRPLA) is a progressive neurodegenerative disorder caused by expanded CAG repeats in the ATN1 gene, characterized by cerebellar ataxia, seizures, tremors, and myoclonus. Although approximately 10% of patients with DRPLA reportedly develop schizophrenia-like psychosis (SLP), the distinct association between the clinical course of DRPLA and SLP remains unclear. This study aimed to elucidate the clinical features of SLP in patients with DRPLA.MethodsWe reviewed 22 cases of pathologically or genetically confirmed DRPLA with SLP, including 21 from the literature and one from our institution. Patient data, including clinical features, treatment information, and disease course, were extracted and analyzed.ResultsThe age of onset was categorized as juvenile (n = 6), early adult (n = 8), and late adult (n = 8). Initially, 10 patients presented with motor symptoms, with six exhibiting psychiatric symptoms and six with both motor and psychiatric symptoms simultaneously. Furthermore, three patients were initially diagnosed with schizophrenia, while four experienced progressive worsening of psychiatric symptoms. The number of CAG repeats ranged from 57 to 76 (mean, 66.0) in the 10 patients with a genetic diagnosis. Summarily, 12 patients received psychotropic medications, with nine showing improvement in delusions and hallucinations.ConclusionSLP can manifest across all DRPLA forms (juvenile-, early adult-, and late adult-onset) and may precede or follow motor symptoms. The clinical course and efficacy of psychotropic medications in patients with DRPLA and SLP suggest a shared pathogenesis between DRPLA and schizophrenia.